WHERE ARE WOMEN? CRITICAL DISCOURSE ANALAYSIS OF WOMEN REPRESENTATION IN EFL TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS - Endah Yunita Setyowati; Elih Sutisna Yanto; Iwan Ridwan (IKIP Siliwangi, 2021)
Studies on the domain of language education indicate that gender stereotypes still exist in teaching-learning media for instance English as a foreign language (EFL) textbook. Since the study within gender stereotypes in EFL textbook has dominantly compared the representation of female and male or men and women, this present study focused on investigating women representation in terms of domestic roles, hobbies, dressing, and social expectation in EFL textbook for Senior High School students published by Ministry of National Culture and Education (MONEC). This study used critical discourse analysis (CDA) to investigate both visual and textual that represent women in term of domestic roles, hobbies, dressing, and social expectation on the selected chapters in the EFL textbook mandated by MONEC as one of the teaching-learning media. The finding reported women still represented stereotypically in term of domestic roles, hobbies, dressing and social expectation in the selected textbook. Keywords: Women Representation, EFL Textbooks, Critical Discourse Analysis, Corpus Study